HYSET: Technological-based physical education learning innovation for strengthening service skills in volleyball - Hidayat, Rahmat; Sholihin, Akhmad Olih; Syamsudar, Bangbang (Universitas Tanjungpura, 2026)
Background. Physical Education learning at the vocational high school level faces the challenge of low active participation and student learning outcomes, especially in the overhand serve material in volleyball. Objectives. This study aims to develop and test the validity of the Hybrid Sports Education Model Teaching Factory (HYSET) learning model, which integrates the Sport Education and Teaching Factory approaches with digital technology support. Methods. This study uses the Research and Development (R&D) method adapted from the Borg & Gall model, which includes the stages of needs analysis, planning, initial product development, expert validation, small group trials, and large group trials. The research subjects comprised 120 tenth-grade students from SMK Negeri Jatiluhur, divided into control and experimental groups. The research instruments include expert validation questionnaires, observation sheets, and volleyball service skill tests. Data were analyzed using a quantitative approach (independent t-test) and descriptive qualitative analysis. Results. The results show that experts deemed the HYSET model feasible, received positive feedback from students, and statistically improved upper serviceability in the experimental group compared to the control group (p < 0.05). In conclusion, the HYSET model is practical and relevant for implementation in technology-based PJOK learning in vocational schools, as it can holistically develop students' technical, socio-emotional, and managerial skills. Conclusion. This model can serve as an adaptive learning alternative to the modern sports industry's evolving times and needs.